The impacts of cultural background on project communication management in international construction projects / He Qing - He, Qing (2022)
This thesis aims to explore intercultural communication in the international construction project in the implementation phase and to examine the responses of international construction projects to cope with the challenges that arise from intercultural communication. A guideline for international construction projects, especially Chinese construction companies, to conduct construction projects in another cultural background is developed in this thesis. There have lots of literature in the project communication field, and there also exist lots of researches related to cultural impacts in the business field. While there has been few of them considered the impacts of cultural factors to project communication in international construction projects or examined the impacts of intercultural communication in intercultural construction projects. This thesis based on this situation, trying to develop insights from the intercultural communication and project management literature to bridge the knowledge gap between cultural background and international construction project communication in term of challenges and the results of their responses to cope with challenges. This thesis adopted a case study research method within the qualitative methodology, semi-structured interviews, documents analysis and observation when the author worked at international construction project A in Tanzania as a human resource manager. A grounded theory approach was applied in the analysis of data .this thesis examined a series of factors that affect intercultural communication in international construction projects and the responses of the project at the organization and individual level to cope with challenges. This thesis revealed the impacts of cultural background to intercultural construction projects by revealing more challenges than opportunities caused by intercultural communication; identifying responses in international construction projects to cope with challenges; revealing the neglect of intercultural communication in international construction projects.all of these aspects make a theoretical contribution to the communication management in international construction projects.